Improvement of solubility and pharmacokinetic profile of hepatoprotector icariin through complexation with HP-γ-cyclodextrin - Ding, Yili; Yu, Bo; Zhou, Shuzhen; Ding, Charles; Zhang, Zhiyuan; Xu, Shufeng; Xu, Zhe (Frontiers in Pharmacology, 2023)
Icariin as a hepatoprotector from Herba epimedii can expand the cardiovascular and cerebral blood vessels, promote hematopoietic functions, enhance immune system, show anti-liver tumor activities, however, its low solubility (0.02 mg/mL) limits its clinic applications as food and medical supplements. Through complexation with HP-γ-cyclodextrin by using a trace amount of water-soluble polymer, the water solubility of icariin was increased by 654 times, which is the best result of the water solubility study of icariin so far. In vitro PK study, the complexation increased the dissolution rate of icariin by 80 times, and the icariin complex can be released 100% in the first few minutes. In vivo dog PK study, through complexation, the Cmax of icariin was increased 4.92 times, the AUC0-120 was increased 19.97 times, and the clearance of icariin was changed from 11.17 to 0.65, and the half-life time was changed from 0.68 hour to 6.38 hour, the relative bioavailability was reached as high as 1997%, indicated that less drug is needed for the same therapeutic effect by using the icariin complex, and the complex can be used as a potential potent hepatoprotector or anti-liver cancer drug.